El primer acuerdo del Nuevo Estado español con la Santa Sede de 7 de junio de 1941 - Marquina, Antonio (UNISCI Discussion Papers, 2015)
El primer acuerdo del Nuevo Estado español con la Santa Sede de 7 de junio de 1941